The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1021/acs.langmuir.7b02441
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Dispersibility of Graphitic Carbon Nitride Particles in Aqueous and Organic Media via a One-Pot Grafting Approach

Abstract: A facile route to synthesize hydrophilically or hydrophobically grafted graphitic carbon nitride (g-CN) is reported. For this purpose, functionalized olefinic molecules with a low polymerization tendency are utilized for grafting onto the surface to preserve the features of g-CN while improving its dispersibility. One-pot, visible light-induced grafting yields highly dispersible g-CNs either in aqueous or organic media. Moreover, functional groups such as amines can be introduced, which yields pH-dependent dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
108
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(115 citation statements)
references
References 49 publications
3
108
0
2
Order By: Relevance
“…Sulfonic acid functionalized g‐CN (g‐CN‐AHPA) was synthesized via cyanuric acid‐melamine complex and surface modification as reported in literature . Modification of g‐CN with AHPA was confirmed via elemental analysis and zeta potential (Table S1, Supporting Information), as well as transmission electron microscopy (Figure S1, Supporting Information), energy‐dispersive X‐ray spectroscopy mapping in scanning electron microscopy (SEM) (Figure S2, Supporting Information) and spectroscopy (Figure S3, Supporting Information).…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…Sulfonic acid functionalized g‐CN (g‐CN‐AHPA) was synthesized via cyanuric acid‐melamine complex and surface modification as reported in literature . Modification of g‐CN with AHPA was confirmed via elemental analysis and zeta potential (Table S1, Supporting Information), as well as transmission electron microscopy (Figure S1, Supporting Information), energy‐dispersive X‐ray spectroscopy mapping in scanning electron microscopy (SEM) (Figure S2, Supporting Information) and spectroscopy (Figure S3, Supporting Information).…”
Section: Methodsmentioning
confidence: 95%
“…It was shown that g‐CN sheets act as reinforcer and photoinitiator in radical mediated hydrogel formation with surface charge being one of the important parameters regarding hydrogel strength . Our group recently developed a one pot grafting method to anchor functional groups on the surface of g‐CN, showing excellent dispersions in aqueous and organic media . In such a way, 3‐allyloxy‐2‐hydroxy‐1‐propanesulfonic acid (AHPA) groups can be grafted onto the g‐CN surface (g‐CN‐AHPA) for enhanced dispersibility in water and lower surface zeta potential, which may lead to the formation of strong hydrogels.…”
Section: Methodsmentioning
confidence: 99%
“…In aktuellen Arbeiten wurden auch kohlenstoffbasierte Nanomaterialien wie graphitisches Kohlenstoffnitrid (g-C 3 N 4 )und C-Dots (CDs) in photobiokatalytischen Anwendungen eingesetzt. [38,39] C-Dots sind quasi-sphärische Partikel mit einem Durchmesser von weniger als 10 nm. [36] g-C 3 N 4 ist ein metallfreier polymerer Photokatalysator mit starker Absorption im Bereich sichtbaren Lichts und einer Bandlücke von etwa 2.7 eV.…”
Section: Grundlagenunclassified
“…The reason lies on the poor dispersibility of most CNs in common solvents, which make them almost non‐processable for (photo)electronic applications . Without ignoring the great progress in this field, mainly by the introduction of new exfoliation methods, the improvement of their dispersibility and more specifically allowing the easy and scalable preparation of well‐dispersed CN materials with enhanced and tunable electronic and light‐harvesting properties is still highly required …”
Section: Introductionmentioning
confidence: 99%